Pengaruh Latihan Jalan Tandem Terhadap Peningkatan Keseimbangan Pada Lansia Di RS Indriati Solobaru - Novianto Agus Prabowo; Sartoyo Sartoyo; Achmad Fariz; Wahyu Teja Kusuma (Jurnal Keperawatan Muhammadiyah, 2023)
Objective:  Stability is the ability of maintaining static and dynamics equilibrium, which influenced the falling incident and the capability in doing everyday activities of elderlies .  The purpose of this study is to analyze the effect of tandem walking exercise for  stability on elderly people.Methods:  This research is quasi experiment with pre and post-test one group design. The samples are 30 people that distributed into one group who were given tandem walking exercise three times a week for two weeks. Assessment of the  stability is assessed using Time Up and Go Test (TUGT). Results:  The result of hypothesis tests with  kolmogorov- smirnov  obtained that there is an impact from tandem walking exercise for  for  stability on elder. Different pre test and post test using paired samples t-test showed p=0.000(p<0.05) which means there is a change o influence. Conclusion:  Tandem walking exercise could improve stability on elderly people.